PENGRUH PENILAIAN PRESTASI KERJA ,DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BBPPMPV BISNIS DAN PARAWISATA SAWANGAN DEPOK - Shella Puspita Sari (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of the study was to determine the effect of partial and simultaneous assessment of work performance, work discipline and motivation on employee performance at BBPMPPV Business and Tourism, Sawangan Depok. This research is associative with a quantitative approach. The population in this study were all employees of the BBPMPPV Business and Tourism, Sawangan Depok, while the sample used in this study was 145 respondents. Data collection techniques by means of questionnaires, and data analysis techniques using instrument test, classical assumption test, regression analysis, coefficient of determination, t-test and f-test. The results showed that partially the work performance appraisal had a positive and significant effect on employee performance, this can be proven from the simple regression value obtained Y=14,283+1,039X1, R Square 29.2%, and the t value of 7,680 > t table 1.9766 with a significant 0.000 <0.05. Partially, work discipline has a positive and significant effect on employee performance, this can be proven from the simple regression value obtained Y=31,543+0,621X2, value R Square is 62.4%, and the t-count value is 15.403 > t table 1.9766 with a significant 0.000 < 0.05. Partially, motivation has a positive and significant effect on employee performance, this can be proven from the simple regression value obtained by Y=31,483+0,617X3, value R Square is 48.1%, and the t-count value is 11.517 > t table 1.9766 with significant 0.000 < 0.05. Simultaneously assessment of work performance, work discipline and motivation have a positive and significant effect on employee performance, this can be proven from the multiple regression value obtained, namely Y=11.097+0.558X1+0.399X2+0.194X3, R Square is 71 %, and the calculated F value is 114.874 > F table 3.06 with a significance of 0.000 <0.05.